Current strategies and future perspectives in biological hydrogen production: A review. (October 2022) - Ramprakash, Balasubramani; Lindblad, Peter; Eaton-Rye, Julian J.; Incharoensakdi, Aran
Abstract: Biohydrogen is a green and eco-friendly energy carrier with the potential to reduce our dependency on fossil fuels. Renewable biohydrogen production from waste biomass sources is potentially cheap; however, large-scale commercial production has not yet been achieved. Problems that need to be tackled include identifying industrially competent microorganisms, and appropriate bioreactor designs enabling novel hybrid methods such as integration of dark fermentation with electro-fermentation and utilization of microbial organisms doped with semiconducting nanomaterials for enhanced production. This review focuses on the production of hydrogen by biological methods, highlighting various fermentation processes, the role of enzymes, and different pretreatment methods. The waste materials used are briefly summarized, and current strategies in biological hydrogen production, including biomimetic and synthetic biology approaches, are assessed for their economic feasibility and their potential to contribute to net zero carbon emission. The lignocellulosic waste and the dynamic membrane bioreactor are the best suitable biomass and bioreactor, respectively for biohydrogen production. The integrated method of dark fermentation and electro-fermentation yields 41% higher hydrogen compared with dark fermentation alone. Finally, this review points out that significant efforts focusing on the development of hybrid fermentation technologies along with the development of novel engineered strains are needed for the commercial-scale production of biohydrogen in the future. Highlights: The combined fermentation methods offer advantages compared to dark fermentation. Lower volumetric yield and O2 sensitivity are major bottlenecks in bio-H2 production. Hybrid fermentation systems increase the yield and efficiency in bio-H2 production.